Overlooked or Late Diagnosed Diseases in Mental Patients Because of Prejudices Report of Two Cases - Arslan, Muhammet Mustafa; Eren, Ali; Çekin, Necmi (The Bulletin of Legal Medicine, 2008)
Patients with psychiatric diseases have higher levels of mortality compared to the normal population. Because underlying diseases could be overlooked due to negative emotional status, the effects of phsycotropic drugs and clinical progression of the current disease. In the current study, we presented two cases in which two schizophrenic patients died because of overlooked organic diseases like late-diagnosed blunt head trauma and undiagnosed acute abdomen. The first case was a schizophrenic 37 years-old male. It was reported that the patient was taken to Psychiatry Hospital because he was incooperable and his general status was poor. It was also notified that he fell to the ground because of diffuculty in walking, an abrasion occurred in right eyebrow, he developed confussion in the 2nd day of the accident, had acute subdural and subarachnoid bleeding in the 4th day, was operated and then died 4 days after the operation. In his autopsy, a lineer fracture in right anterior fossa and subdural and subarachnoidal bleedings were detected. Finally the patient was reported to die from cerebral hemorrhage due to blunt skull trauma. The second case was schizophrenic 35 years-old male. It was reported that he suffered from discomfort and had nausea and vomiting. Then the patient was taken to a clinic, injected an unknown drug and sent to home. In the following day, the patient died when he was being taken to the clinic again due to his worsening general status. His autopsy showed peritonitis and perforation in stomach. It was decided that the patient died from peritonitis due to gastric perforation. In conclusion, complete systemic physical examination and consultations should be performed in psychiatric in-patients who couldn’t give reliable history and express their complaints in order no to overlook accompanying organic disorders. Key words: Psychiatric in-patients, differential diagnosis, forensic medicine